2019
DOI: 10.1155/2019/8749090
|View full text |Cite
|
Sign up to set email alerts
|

Amifostine Suppresses the Side Effects of Radiation on BMSCs by Promoting Cell Proliferation and Reducing ROS Production

Abstract: This study is aimed at investigating the effect of amifostine (AMI) on rat bone marrow stromal stem cells (BMSCs) exposed to 2 Gy radiation. The BMSCs were divided into four groups, namely, group A that received 0 Gy radiation, group B that received 0 Gy radiation and AMI, group C that received 2 Gy radiation, and group D that received 2 Gy radiation and AMI. The proliferation, apoptosis, and distribution of BMSCs in the cell cycle, along with their osteogenesis ability, adipogenesis ability, and ROS productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Although the mechanisms of amifostine and CBLB502-mediated radioprotection are poorly understood, 39 they are both likely to have a cytoprotective effect and rapid response against IR-induced stress within several hours, 5 , 40 with achieving complex radiation-cytoprotective effects by interfering with genes involved in scavenging free radicals, cell cycle regulation, apoptosis, and inflammation. 6 , 7 , 41 - 46 However, nilestriol requires a longer time, usually hours or days, to exert its protective effects, and its post-irradiation mechanism does not involve primary radiation-induced cellular processes. 3 , 9 These differences in reaction time and mechanism may explain the similarities between amifostine and CBLB502 in terms of the influence on IR-induced RNAs, which was distinct from that of nilestriol.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms of amifostine and CBLB502-mediated radioprotection are poorly understood, 39 they are both likely to have a cytoprotective effect and rapid response against IR-induced stress within several hours, 5 , 40 with achieving complex radiation-cytoprotective effects by interfering with genes involved in scavenging free radicals, cell cycle regulation, apoptosis, and inflammation. 6 , 7 , 41 - 46 However, nilestriol requires a longer time, usually hours or days, to exert its protective effects, and its post-irradiation mechanism does not involve primary radiation-induced cellular processes. 3 , 9 These differences in reaction time and mechanism may explain the similarities between amifostine and CBLB502 in terms of the influence on IR-induced RNAs, which was distinct from that of nilestriol.…”
Section: Discussionmentioning
confidence: 99%
“…Amifostine is a synthetic antioxidant shown to lessen tissue damage by binding free radicals and promoting tissue repair [66]. It has been shown in both animal models to protect bone quality and healing, though most of this work focuses on the mandible rather than long bones [67][68][69]. Additionally, amifostine has been shown to be radioprotective to the physis in combination with misoprostol, selenium, and pentoxifylline [70].…”
Section: Future Directions For Fracture Prevention: Medical Erapiesmentioning
confidence: 99%
“…Amifostine is a radio-protective agent that acts by scavenging free radicals generated by ionizing radiation. A recent in vitro study of rat bone marrow stem cells with or without radiation and amifostine showed that the addition of amisfostine to irradiated cells decreased the amount of reactive oxygen species and DNA damage and increased the levels of cellular proliferation, which is promising [80]. Additionally, Zhang and colleagues showed that in an in vivo rat model, by reducing DNA damage, amifostine may decrease the differentiation of osteoclast precursor cells into differentiated osteoclasts.…”
Section: Amifostinementioning
confidence: 99%